Evaluation of phlebitis adverse event occurrence in patients of a Clinical Inpatient Unit* - Furlan, Maryana da Silva; Lima, Antônio Fernandes Costa (Revista da Escola de Enfermagem da USP, 2021)
Objective: To analyze the causes and reasons associated with the occurrence of phlebitis in a Inpatient Medical Unit in a large and private general hospital. Method: Quantitative, exploratory-descriptive, retrospective and documentary research, carried out by consulting the electronic forms of notification of the occurrence of phlebitis in 2017. Results: A total of 107 phlebitis related to 96 patients were reported, most of them (91.7%) with phlebitis, being male (53.1%), aged 60-69 years old (23.0%) and with a hospital stay of less than four days (30.2%). Most (68.2%) of the notifications were made by nurses, with the occurrence of phlebitis predominating in devices with less than 24h (38.3%); with the classification of phlebitis grade 2 (45.8%); with antibiotics infusion (46.7%); with the location of the bed far from the nursing station (52.3%); and with the presence of a companion (82.2%). The damage classification indicated that 93.5% of the patients suffered mild damage, 4.7% moderate damage and 1.9% did not suffer any damage. Conclusion: Knowing the causes and reasons associated with the occurrence of phlebitis can support decision-making, management and care processes regarding investments in preventive or risk mitigation strategies.